The impact of cultural fusion on society inThe first (132-232هـ/749-847م) Abbasid era - dr.Afrah Raheem Ali Al-Ghalibi/ (Journal of College of Education, 2026)
One of the most prominent features of the Arab-Islamic civilization in the Abbasid era was the emphasis on culture, the significant development in knowledge, and the widespread prosperity of education. Cultural fusion is an advanced civilizational phenomenon in the lives of nations and peoples. This concept indicates the sophistication of individuals in human society and their fusion within the concept of the human melting pot. There is hardly a people or nation that is devoid of intellectual and cultural fusion among its members. Perhaps Islamic culture embraced the heritage of previous nations that was threatened with extinction and disappearance. Without it, people in the modern era would not have known anything about the Greek, Indian, and ancient works that libraries are filled with copies of. It can be said that the negative impact of this cultural openness was limited in comparison to the positive benefits Muslims achieved as a result. Moreover, sincere Islamic scholars confronted the deviant ideas that spread throughout different eras. While cultural integration often leads to harmony, it can also lead to conflict when different values and practices conflict. These themes highlight the complexity of cultural integration and its important role in shaping contemporary societies. Embracing cultural integration fosters mutual respect and appreciation between different cultures.